Colourimetric analysis of some powdered medicinal herbs from Ogbomoso, Nigeria - Adepoju Ogunkunle; Jennifer Ideh (AOSIS, 2019)
Background: The organoleptic evaluation of herbal drugs is as old as science, but the authentication of herbs on the basis of their fluorescence characteristics is difficult and sometimes impracticable because humans are limited by their sense of colour recognition. Aim: This article undertakes a computer-aided examination of some powdered herbal materials with a view to characterising them calourimetrically, thus providing a reliable organoleptic clue for their authentication, against possible misidentification. Setting: Research was conducted in Ogbomoso, Nigeria. Methods: Seventeen herbal materials (i.e. stem bark, root/root bark, vines, fruit calyx, leaf sheath and seed) used for two traditional powdered drugs were collected and pulverised into powders. Their colours were digitised by scanning the surface of the powders in petri dishes using a CamScanner installed on a Samsung Galaxy Tablet 10.1 Model 7500, and were qualitatively and quantitatively analysed by uploading the images into the online Cool Hypertext Preprocessor (Cool PHP) software tool, setting the number of colours at five, thus giving consideration to only five dominant colour shades in each image, all expressed as hexadecimal codes. The codes were uploaded into Chir.ag/art, another online tool, to read off the colour names. The relative mean percentage, frequency and relative colour intensity (RCI) of each colour shade were calculated, and the colour with the highest RCI was taken as the first or typical colour of each herb. Results: Nine of the 62 colours observed, namely Lucky, Sandrift, Cannon Pink, Potters Clay, Mandalay, Ferra, Domino, Russet and Roti, were highly restricted in distribution, each being the first or typical colour in only one species of the herbs (i.e. Enantia chlorantha, Garcinia kola, Hibiscus sabdariffa, Khaya senegalensis, Sarcocephalus latifolius, Sorghum bicolor, Theobroma cacao, Uvaria chamae and Zanthoxylum zanthoxyloides respectively). These colours were therefore substantially diagnostic of those herbs. Another nine colours among the most frequently observed colours and the number of species that had them were Pesto (9), Shadow (8), Driftwood (8), Barley Corn (5), Domino (4), Roman Coffee (4), Cape Palliser (4), Himalaya (4) and Husk (4); these were less diagnostic of the herbs in question. Based on the distribution of these colours, a diagnostic PHP colour chart was constructed for the authentication of the powdered medicinal herbs. Conclusion: Powders of the 17 medicinal herbs analysed have been characterised colourimetrically with each species being unambiguously diagnosed. The study has therefore circumvented the subjectivity of the human sense of colour recognition in medicinal herb authentication.